2012
DOI: 10.1016/j.jcis.2012.07.078
|View full text |Cite
|
Sign up to set email alerts
|

Mass-mobility characterization of flame-made ZrO2 aerosols: Primary particle diameter and extent of aggregation

Abstract: Gas-borne nanoparticles undergoing coagulation and sintering form irregular or fractal-like structures affecting their transport, light scattering, effective surface area and density. Here, zirconia (ZrO 2 ) nanoparticles are generated by scalable spray combustion, and their mobility diameter and mass are obtained nearly in-situ by differential mobility analyzer (DMA) and aerosol particle mass (APM) measurements. Using these data, the density of ZrO 2 and a power law between mobility and primary particle diame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
69
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 71 publications
(81 citation statements)
references
References 51 publications
12
69
0
Order By: Relevance
“…As discussed by Eggersdorfer et al (2012a), the average projected area (a a ) of fractal-like aggregates can be related to the number of their constituent primary particles n va by the following power-law (Medalia 1967) correlation:…”
Section: Theorymentioning
confidence: 99%
See 4 more Smart Citations
“…As discussed by Eggersdorfer et al (2012a), the average projected area (a a ) of fractal-like aggregates can be related to the number of their constituent primary particles n va by the following power-law (Medalia 1967) correlation:…”
Section: Theorymentioning
confidence: 99%
“…1994;Park et al 2004aPark et al , 2004b; here D a;opt D 1800 kg/m 3 is used. The mobility diameter (d m ) of aggregates in the free molecular (Meakin et al 1989) and transition (Rogak et al 1993) regimes is approximately equal to the projected area equivalent diameter (d a ) of the aggregates (d a D 2 ffiffiffiffiffiffiffiffiffiffi a a =p p ) (Eggersdorfer et al 2012a). Park et al (2004a,b) showed that this approximation is accurate for diesel aggregates of up to D a;meas nm.…”
Section: Theorymentioning
confidence: 99%
See 3 more Smart Citations